A Cipp Model-Based Approach Evaluation and Improvement Of The Program Of Profil Pelajar Pancasila: Answering Challenges In Character Education - Zainuddin, Zurahmah (JED (Jurnal Etika Demokrasi), 2025)
The Structure of the Merdeka Curriculum focuses on the formation of The Pancasila Student Profile (PPP), which is a guide in developing standard content, processes, and assessments at every level of education. The Project Program for Strengthening Pancasila Student Profile (P5) is applied to basic to medium education, aiming to form students' characters under the values of Pancasila and respond to the challenge of the Industrial Revolution 4.0. Method: This study aims to evaluate the effectiveness of the P5 program and suggest repairs. The method in this study uses the CIPP evaluation model (context, input, process, product). The application of this method is based on the suitability of the program with the P5 module compiled by the team, and conducted depth interviews with the school principal, vice principal, and curriculum vice principal as stakeholders and analyzed the P5 report card document. Results: The evaluation results show that P5 is effective in building the character of students through the integration of independence values, cooperation, creativity, and democracy. Based on the P5 report card, students of SMP Negeri 1 Makassar are categorized as follows: 70.7% of students are categorized as Developed as Expected (BSH); 22% are categorized as Very Developed (SB); 7.3% are categorized as Start Developed (MB); and there is no student categorized as Not Developed (BB). However, there is a challenge faced in the implementation of the Pancasila Student Profile Program, such as the difference in mindsets between teachers, delays in disbursing funds, and the need for a more objective assessment rubric. In addition, the implementation time is needed from the center and more varied theme guidelines. Conclusions: This evaluation suggests that the development of the assessment rubric and improvement of operational procedures is carried out to increase the effectiveness of the program. Although the final product is not always physical, the main focus of P5 is a change in attitudes and commitment of students to the values raised in the project.